Simulation of Induction Traction Drive with Supercapacitor Energy Storage System Test Bench - Stana, Girts; Brazis, Viesturs; Apse-Apsitis, Peteris (Electrical, Control and Communication Engineering, 2015)
The paper describes the application of supercapacitor energy storage system for induction traction drive test bench that replaces a real electric public transport for performing testing and researches. The suitability and usage of such bench for research purposes is explained and the importance of the development of software mathematical model for performing simulations to be done before physical implementation measures is reasoned. The working principle of the bench and applied components are described. A virtual model of the bench was built and simulations were performed using Matlab/Simulink software. The basic topology of the virtual bench model is described as well. The calculations of this work show the scaling of supercapacitor energy storage system by setting different limits of working voltage range in order to adjust them to test bench parameters, whereas the modelling compares two simulation cases – the application of less supercapacitors and the application of more supercapacitors with the same common rated voltage. The autonomous mode simulations were also performed. Simulation results are analyzed and recommendations for the application of the supercapacitor energy storage system, with respect to initial supercapacitor circuit voltage, are given.